A randomized controlled trial to study the efficacy of 1% vs. 2% lignocaine in topical airway anesthesia in routine bronchoscopy procedures - Danny Prasad; Prince James; Richa Gupta (The Egyptian Journal of Bronchology)
Abstract Background Bronchoscopists worldwide still prefer to use 2% lignocaine as the preferred topical airway anesthetic. The minimum concentration of lignocaine used during flexible bronchoscopy to prevent uncontrolled coughing is still unclear. This double-blinded, randomized controlled trial compared the efficacy of 1% and 2% lignocaine solutions for topical anesthesia during routine flexible bronchoscopy procedures. Five hundred patients were randomized to receive either 1% or 2% lignocaine. For topical airway anaesthesia, lignocaine was administered in aliquots of 2 ml each in a spray-as-you-go technique. The study’s primary outcome was the assessment of cough objectively by the consultant proceduralist, respiratory nurse, and assisting respiratory therapist. The subjective cough evaluation was taken from the patient using the cough visual analog score (VAS). The key secondary outcomes investigated were the total lignocaine dose, complications due to lignocaine administration, overall procedure satisfaction assessed by bronchoscopist (VAS), and patient (VAS) pain score. Results The cough VAS scores, as assessed by patients in both groups (2% vs. 1%), were similar (28.4 vs. 28.0 [p − 0.997]). The cough VAS scores evaluated by the bronchoscopist (31.4 vs. 34.5 [p − 0.116]), respiratory nurse (31.3 vs. 34.3 [p − 0.182]), and therapist (31.7 vs. 34.3 [p − 0.209]) were slightly higher in the 1% arm. The pain ratings by the patient were similar between the two groups (0.82 vs. 0.92 [p − 0.135]). The overall satisfaction of bronchoscopists was slightly higher in the 1% arm (35.01) vs. 2% arm (32.18) [p − 0.167]. The cumulative dose in the 1% lignocaine arm was 253 mg compared to 490 mg in the 2% lignocaine arm. There was no adverse event related to lignocaine overdose in either arm. Conclusions One percent of lignocaine was found to be as effective as 2% lignocaine for topical anesthesia during routine flexible bronchoscopy procedures, and it was achieved at a significantly lower dose of lignocaine in the 1% arm. So, in flexible bronchoscopy, we suggest 1% lignocaine as the preferred topical airway anesthetic agent over 2% lignocaine.